ORMAS DALAM POLITIK (HUBUNGAN PATRON KLIEN PEMUDA PANCASILA DAN PASANGAN ERAMAS DALAM PILGUB SUMUT TAHUN 2018) - Christiano Singarimbun, Hagai Zefanya; Ali Azhar, Muhammad; Noak, Piers Andreas (Jurnal Nawala Politika, 2019)
ABSTRACT__   The theory of Patron Client proposed by James Scott is used_in this study_The_results of this study showed_that:_First, Pemuda Pancasila gave their loyalty and devotion to ERAMAS couple by contributing in_the_form_of_contributions_to_the_regional administrators, social activities and direct activities for the community to the success of ERAMAS Couple. Second, the relationship of Patron Client established between Pemuda Pancasila and ERAMAS created a mutually beneficial relationship with the exchange of rewards such as granting access in the provincial government, granting positions and facilitating licensing and vice versa Pemuda Pancasila provided loyalty and services. Third, the Governor election of North Sumatra in 2018 is a momentum for the Pemuda Pancasila to support and win the Governor candidate who was the best cadre of the Pemuda Pancasila.   Keyword: Pemuda Pancasila, Patron Client, the Governor Election of North Sumatra in 2018